Effect of Virtual Manipulatives on Students Academic Success in Teaching Integers - Yurt, Aysun; Kepceoğlu, İbrahim (Journal of Computer and Education Research, 2025)
This study investigates the effect of virtual manipulatives on 7th-grade students’ academic achievement in the multiplication and division of integers. A quasi-experimental design with a post-test control group was employed. The study involved 30 students assigned to experimental and control groups based on readiness level equivalence. The experimental group received instruction supported by virtual manipulatives, while the control group was taught using traditional teacher-centered methods. Data were collected through a readiness test and two researcher-developed achievement tests on multiplication and division of integers. Independent samples t-tests were used to analyze the data. The findings indicated a statistically significant improvement in the multiplication performance of the experimental group compared to the control group, whereas no significant difference was found in division performance. The results suggest that virtual manipulatives can effectively enhance students’ conceptual understanding and success in specific mathematical operations.